Making a difference in theory : the theory question in education and the education question in theory - Biesta, Gert (Milton Park, Abingdon, Oxon : Routledge, 2014)
'Making a Difference in Theory' brings together original work from an international group of authors on the roles of theory in educational research and practice. The book discusses the different roles theory plays, can play and should play, both from a historical perspective and in light of contemporary discussions and developments. Particular attention is paid to the question of whether there are or should be distinctively educational forms of theory and theorising.
Includes bibliographical references and index.
Keywords: Education -- Philosophy; Education -- Research -- Methodology